Validity and reliability of the Persian version of the nurse spiritual care therapeutics scale (NSCTS) - Merati-Fashi, Fatemeh (BMC Palliat Care, 2021)
BACKGROUND: Dealing with the spiritual needs of patients has been recognized as one of the principles of holistic care in nursing. Therefore, it is necessary for nurses to deal with the spiritual issues of patients. Also, a valid and reliable scale is needed to measure nurse-provided spiritual care. So the purpose of this study was to determine the validity and reliability of the Persian version of the “Nurse Spiritual Care Therapeutics Scale” in Iranian nurses. METHOD: In a methodological study, English version of the Nurse Spiritual Care Therapeutics Scale was translated into Persian by forward–backward translation procedure. Face validity was assessed by cognitive interview, and content validity was assessed by a panel of experts. In addition, construct validity was assessed by exploratory factor analysis. The participants were 188 nurses working in different adult wards. Reliability was measured using the Cronbach’s alpha and stability reliability was assessed using the internal correlation coefficient (ICC). RESULTS: In assessing the construct validity, two factors with eigenvalues greater than 1 were identified, which explained 58.47% of the total variance. Cronbach’s alpha value was 0.932, and ICC was 0.892. CONCLUSION: As a result, the Persian version of the Nurse Spiritual Care Therapeutics Scale shows a good validity and reliability. Therefore, this scale can be used to evaluate spiritual care at the bedside in Iran.